(untitled) (Journal Of Educational and Psychological Researches, 2012)
The university’s lecturers are effective instrument in building the march of science and knowledge, they are establish the right path approach in scientific research which contributes to the formation and develop of the society, the verifying and acceptance of objectives, are not the only matter that dominated concerns of lecturers, there is something wait him, the remaining of his life and stability, that would raises anxiety ,anxiety what will coming years carry it, it is future anxiety, because the size of the problems and psychological stress, all the self possibilities are available to the university’s lecturers, these are the importance of study to identify the negative impact which created by the conditions that country experienced it , future direction’s of the lecturer. The objectives of current study were 1- identify future anxiety in university’s lecturers 2—identify the psychological stress which exposed by university’s lecturer. 3 - Is there a statistically significance differences related gender (male – female). 4- Is there a relationship between the future anxiety and stress. The participants of current study were university’s lecturers the academic year on (2010-2011) to achieve the objectives of current study the researcher structured scale to investigate future anxiety, also used Alshhebe (2005) to investigate the psychological stress. (400) lecturers answered two questions. The results were. • The university’s lectures had not future anxiety. • The university’s lectures exposed different psychological stress. • There was not difference significance between male and female. • There was relationship between stress and future anxiety. The researcher suggested some recommendations and future study.